2022
DOI: 10.3390/antibiotics11020207
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Biological Evaluation of Novel Benzamidine Derivatives: Newer Antibiotics for Periodontitis Treatment

Abstract: Periodontal disease (PD) is complex polymicrobial disease which destroys tooth-supporting tissue. Although various synthetic inhibitors of periodontitis-triggering pathogens have been recognized, their undesirable side effects limit their application. Hence, the present study intended to perform the synthesis, characterization, antimicrobial evaluation, and cytotoxicity analysis of novel benzamidine analogues (NBA). This study involved the synthesis of novel imino bases of benzamidine (4a–c), by reacting diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
4
5
0
Order By: Relevance
“…The antimicrobial and cell viability research on novel benzamidine analogues (NBA) indicated that presence of NO 2 and Cl (electron withdrawing groups) in compounds 3a and 3b, respectively on 4 th position of benzyl ring offers significant MIC, MBC and safety. Findings of current investigation were also found to agree with the findings of other investigations on inhibitory response of benzamidines towards P. gingivalis [1][2][3]23,24]. Therefore, the current cell viability and antimicrobial research findings supports significant safety and efficacy of NBA.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The antimicrobial and cell viability research on novel benzamidine analogues (NBA) indicated that presence of NO 2 and Cl (electron withdrawing groups) in compounds 3a and 3b, respectively on 4 th position of benzyl ring offers significant MIC, MBC and safety. Findings of current investigation were also found to agree with the findings of other investigations on inhibitory response of benzamidines towards P. gingivalis [1][2][3]23,24]. Therefore, the current cell viability and antimicrobial research findings supports significant safety and efficacy of NBA.…”
Section: Resultssupporting
confidence: 88%
“…Hence based on high docking score of molecules L, 1, 1a, 2a-c and 3a-c, it was decided to carry out the synthesis, optimization and characterization of compounds 3a-c and determine their inhibitory potential (MIC and MBC) against P. gingivalis, followed by cytotoxicity against healthy human cells (HEK 293). Present study successfully synthesized and elucidated the physical and chemical properties of azetidinones, which were also correlated with the other studies [18,23,24]. Similar procedures and results were also highlighted by other studies [30,31].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Synthesis of 10,19-diethyl- [19,20]. Briefly, hydrazinated derivative of irinotecan 1 {(that was obtained after esterification and hydrazination of irinotecan (CPT-11)} was refluxed with chlorobenzaldehyde in equimolar concentration for 8 h. For the reaction, just quantity sufficient (Q.S.)…”
Section: Methodsmentioning
confidence: 99%
“…Recently various antibacterial agents integrated with heterocyclic frameworks such as quinazoline [12, 13], coumarin [14, 15], pyrazole [16, 17], imidazole [18, 19], flavones [20, 21], benzimidine [22, 23] etc. were identified as effective antibacterial drugs.…”
Section: Introductionmentioning
confidence: 99%